Body Image Model Based On The Object Relations An Mediating Role Of The Personality And Ego Strength In Applicants Of Cosmetic Surgery - Oveisi, Helia; Monirpour, Nader; Zargham Hajebi, Majid (International Journal of Applied Behavioral Sciences, 2021)
Introduction:The decision to have cosmetic surgery is greatly affected by psychological problems. The high number of cosmetic surgery requests, which can be one of the consequences of psychological damage in the stages of mental development, shows the significance of paying attention to the role of thematic relationships, personality organization and ego strength. This study aimed to explain the body image model based on object relations, and the mediating role of personality and ego strength in people referring to cosmetic surgery centers.Method:This study was conducted through a descriptive -correlational approach. The statistical population included all people who referred to Vanak Cosmetic Surgery Center in Tehran in spring and summer of 2020, a sample of 350 subjects were selected by available sampling method. Data were collected through Body-Self Relations Questionnaire, Bell's Object Relations Inventory, the Kernberg’sInventory of Personality and Psychosocial Inventory of Ego-strengths. The data were analyzed by a path analysis of structural equation modeling.Results: The structural equation modelling of body image, object relations, personality organization and ego strength directly and indirectly demonstrated significant fitness (RMSEA: 0.07). Among indirect paths, mediator variables including personality organization and ego strength were significant.Conclusion: Injury in the initial object relations can affect thecreation of a negative body image among people seeking cosmetic surgery by creating a negative feeling in the person and then by affecting the personality organization and ego strength.Declaration of Interest: None